Stabilizing world commodity markets : analysis, practice, and policy - Adams, F. Gerard; Klein, Sonia A.; Ford Foundation (Lexington, Mass. : Lexington Books, 1978)
The issue of commodity market stabilization have become central not only to the North-South dialogue and the new international economy order sought by the developing world but also to the summit negotiations among the industrial countries.
Representative selection of papers presented at a conference held at Airlie, Va., Mar. 17-20, 1977, and sponsored by the Ford Foundation.
Bibliographies and index.
oo 16/10/2018
Loans
Keywords: Commodity control; Price regulation